Mixed agrophytocenose as a reserve of increase of production of fodder grain and more rational use of the land area - Yu. A. Lapshin (Аграрная наука Евро-Северо-Востока)
The results of studies on the comparative efficiency of cultivation of single-species, binary and polycomponent agrophytocenoses on sod-podzolic soils under the conditions of the Republic of Mari El are reflected. It has been established that the simulated agrophytocenoses with different ratios of peas and barley in terms of productivity of the produced grain mass are superior to single-species crops of gorookh. The most productive (grain yield 4.48 t/ha, including 3.31 t/ha peas, 7.3 t/ha protein harvest) and biologically effective in terms of the ratio of land equivalents (LER = 1.22) was a simulated agrophytocenosis involving peas Bogatyr (85%) and barley Risk (15%). The increase in barley from 15 to 35% (from the sowing of the crop in its pure form) led to a decrease in both the proportion of peas in the grain crop yield and the biological effectiveness of the mixed crop (LER decreased from 1.22 to 1.0). A close relationship (r = - 0.76-0.82) between the cenotic activity of barley and pea in mixed agrophytocenoses was established. When cultivating mixed varietal agrophytocenoses of spring wheat, the architectonics of the structure of the productive stemstalk changed, and the competitive interrelationships among the plants were weakened. On the yield of grain in the years favorable for moistening the soil, the modeled mixed agrophytocenosis [Priokskaya (5) + Krepysh (1)] significantly exceeded the pure-grade crops of Krepysh and Priokskaya. In this agrophytocenosis, the value of LER was higher than 1, but it had a pronounced tendency to decrease from 1.16 on an unfertilized background to 1.12 on the background of N45P45K45, 1.08 for N60P45K45 and 1.06 for N90P45K45. Binary agrophytocenoses of winter crops (triticale and wheat) in comparison with single-species crops were not very effective (LER = 1.00 ... 1.11). In contrast, the cultivation of poly-species winter grain agrophytocenoses with the participation of triticale, wheat and rye indicates a more rational use of environmental resources (LER = 1.15 ... 1.29). Cultivation of simulated mixed agrophytocenoses is an affordable and cheap way of producing high-quality forage grains. Grain productivity of multicomponent agrophytocenosis is determined by a set of constituent crop-components.